Spatial distribution of submerged aquatic vegetation in An Chan coastal waters, Phu Yen province using the PlanetScope satellite image - Hang, Nguyen Thi Thu; Hoa, Nguyen Thai; Tu, Nguyen Van; Lam, Nguyen Ngoc (Vietnam Journal of Earth Sciences, 2019)
Seaweed and seagrass form marine submerged aquatic vegetation (SAV), which plays an essential role in economic development and ecological protection in coastal areas. In this study, PlanetScope (PS )imaging data was combined with in situ samplings to demonstrate their ability to map SAV distribution in An Chan commune, Tuy An district, Phu Yen province, Central Vietnam. Thanks to data pre-processing by Lyzenga’s algorithm and the masking in PS image allow us to remove partly the signals of spectral noises from sun glint effect as well as other random noises. The analysis and accuracy assessment of SAV classification by four different techniques: DII, enhanced DII, BRI and enhanced BRI were alternately performed. The overall accuracy in the accuracy assessment of SAV classification by the above techniques were alternately 83.33%, 88.58%, 86.17%, and 92.52% respectively. Kappa coefficients in the accuracy assessment of SAV classification by the above techniques were alternately 0.77, 0.84, 0.81 and 0.90 respectively. The results of SAV classification by enhanced BRI technique provided the best accuracies and will be chosen for assessing the distribution of Submerge Aquatic Vegetation (SAV) canopies in An Chan coastal waters from PS satellite image. The seagrass beds in An Chan is spread along the coast as well as lie close to the coast of islets. Whereas, the seaweed meadows lie in deeper waters and in the foot of the reefs in 3–4m deep. The total seagrass area in An Chan region was approximately 12.22 ha, with 10.93 ha seagrasses in My Quang, 1.18 ha in Hon Chua and 0.11 ha in Hon Dua. The total seaweed area in An Chan region was approximately 50.32 ha, with 20.20 ha seaweed meadows in My Quang, 22.8 ha in Hon Chua, 5.72 ha in Hon Dua and a small part of 1.60 ha in underwater small reefs.